Using the best of two worlds: A bio‐economic stock assessment ( BESA ) method using catch and price data - Kira Lancker; Rudi Voss; Fabian Zimmermann; Martin F. Quaas (Fish and Fisheries, 2023)
Reliable stock assessments are essential for successful and sustainable fisheries management. Advanced stock assessment methods are expensive, as they require age‐ or length‐structured catch and detailed fishery‐independent data, which prevents their widespread use, especially in developing regions. Furthermore, modern fisheries management increasingly includes socio‐economic considerations. Integrated ecological‐economic advice can be provided by bio‐economic models, but this requires the estimation of economic parameters. To improve accuracy of data‐limited stock assessment while jointly estimating biological and economic parameters, we propose to use price data, in addition to catches, in a new bio‐economic stock assessment (‘BESA’) approach for de‐facto open access stocks. Price data are widely available, also in the Global South. BESA is based on a state‐space approach and uncovers biomass dynamics by use of the extended Kalman filter in combination with Bayesian estimation. We show that estimates for biological and economic parameters can be obtained jointly, with reliability gains for the stock assessment from the additional information inherent in price data, compared to alternative assessment methods for data‐poor stocks. In a real‐world application to Barents Sea shrimp ( Pandalus borealis , Pandalidae), we show that BESA benchmarks well also against advanced stock assessment results. BESA can thus be both a stand‐alone approach for currently unassessed stocks as well as a complement to other available methods by providing bio‐economic information for advanced fisheries management.

German fishery’s adaptation to historic events, Western Baltic Sea, 1890–1950 - Karoline Schacht; Rudi Voss (Ambio, 2023)
Marine social-ecological systems (SES) have been providing important cultural, social, and economic services for many centuries. They are, however, increasingly threatened by fast changing environmental, ecological, and socio-economic conditions. As historical marine research is increasingly developing into a multidisciplinary endeavour, it offers outstanding points of departure to analyse historic events and the response and adaptation of the respective SES. Such knowledge helps to inform today’s fisheries management and promotes successful management of changing ecosystems. Here, we compile and analyse historical data (1890–1950) of the German Western Baltic Sea fishery SES. This period is characterised by a series of strong impacts due to political, technological, economic, and ecological changes, such as two world wars, a global economic crisis, and other economic or ecological disasters. In our opinion, potential negative effects of those events were in the past attenuated by the system’s high capacity to adapt. However, most of the fishers´ historic options on how to respond and adapt have recently become no longer available. New threats (e.g. climate change) have emerged instead. We conclude that today’s fisheries management needs to integrate options of adaptation by exhausting all present or future opportunities. Adaptive fisheries management should not only focus on environmental change but need to include socio-economic change as well.

Quantifying socio‐economic novelty in fisheries social‐ecological systems - Yosr Ammar; Rudi Voss; Susa Niiranen; Thorsten Blenckner (Fish and Fisheries, 2022)
Socio‐economic development has shaped fisheries social‐ecological systems (SES) worldwide across different scales. No work has yet undertaken how this development led to novel, not experienced before, systems structure in marine SES. Here, we quantify socio‐economic novelty as the degree of dissimilarity relative to a specific spatiotemporal baseline in the Baltic Sea fisheries SES between 1975 and 2015. We used catch by "gears," catch by "commercial groups" and trade ("import" and "export") as respective indicators of novelty at national, regional and international governance levels. We found that socio‐economic novelty increased over time nonlinearly in relation to the 1975–1979 baseline. The contribution to total novelty shifted from the dominance of “gears” and “commercial groups” in the late 1990s and early 2000s to “import” and “export” after the mid‐2000s, i.e. from national and regional levels to the international level. The fastest increase in novelty occurred with the trade dominance shift, primarily related to monetary value rather than quantity. Spatially, novelty emerged with a large difference across countries, and a major contribution by Sweden, Denmark and Poland. We identified the influence of different management interventions and governance actions on the emergence of novelty in the Baltic SES. The decreasing socio‐economic novelty at national and regional levels could indicate reduced variability due to management intervention in recent years which might decrease SES resilience to shocks. Calculating socio‐economic novelty and studying its drivers at different scales could provide a better understanding of SES complexity and inform urgently needed adaptation and transformation towards sustainable future pathways.

High-resolution mapping of rachis nodes per rachis, a critical determinant of grain yield components in wheat - Kai P. Voss-Fels; Gabriel Keeble-Gagnère; Lee T. Hickey; Josquin Tibbits; Sergej Nagornyy; Matthew J. Hayden; Raj K. Pasam; Surya Kant; Wolfgang Friedt; Rod J. Snowdon; Rudi Appels; Benjamin Wittkop (Theoretical and Applied Genetics, 2019)

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Ecological-Economic Fisheries Management Advice—Quantification of Potential Benefits for the Case of the Eastern Baltic COD Fishery - Rudi Voss; Martin F. Quaas; Max T. Stoeven; Jörn O. Schmidt; Maciej T. Tomczak; Christian Möllmann (Frontiers in Marine Science, 2017)

It is the economy, stupid! Projecting the fate of fish populations using ecological–economic modeling - Martin F. Quaas; Thorsten B. H. Reusch; Jörn O. Schmidt; Olli Tahvonen; Rudi Voss (Global Change Biology, 2016)
Four marine fish species are among the most important on the world market: cod, salmon, tuna, and sea bass. While the supply of North American and European markets for two of these species – Atlantic salmon and European sea bass – mainly comes from fish farming, Atlantic cod and tunas are mainly caught from wild stocks. We address the question what will be the status of these wild stocks in the midterm future, in the year 2048, to be specific. Whereas the effects of climate change and ecological driving forces on fish stocks have already gained much attention, our prime interest is in studying the effects of changing economic drivers, as well as the impact of variable management effectiveness. Using a process‐based ecological–economic multispecies optimization model, we assess the future stock status under different scenarios of change. We simulate (i) technological progress in fishing, (ii) increasing demand for fish, and (iii) increasing supply of farmed fish, as well as the interplay of these driving forces under different scenarios of (limited) fishery management effectiveness. We find that economic change has a substantial effect on fish populations. Increasing aquaculture production can dampen the fishing pressure on wild stocks, but this effect is likely to be overwhelmed by increasing demand and technological progress, both increasing fishing pressure. The only solution to avoid collapse of the majority of stocks is institutional change to improve management effectiveness significantly above the current state. We conclude that full recognition of economic drivers of change will be needed to successfully develop an integrated ecosystem management and to sustain the wild fish stocks until 2048 and beyond.

Variability of larval Baltic sprat ( Sprattus sprattus L.) otolith growth: a modeling approach combining spatially and temporally resolved biotic and abiotic environmental key variables - HANS‐HARALD HINRICHSEN; RUDI VOSS; BASTIAN HUWER; CATRIONA CLEMMESEN (Fisheries Oceanography, 2010)
Plankton sampling was conducted in the Baltic to obtain sprat larvae. Their individual drift patterns were back‐calculated using a hydrodynamic model. The modelled positions along the individual drift trajectories were subsequently used to provide insight into the environmental conditions experienced by the larvae. Autocorrelation analysis revealed that successive otolith increment widths of individual larvae were not independent. Otolith increment width was then modelled using two different generalized additive model (GAM) analyses (with and without autocorrelation), using environmental variables determined for each modelled individual larval position as explanatory variables. The results indicate that otolith growth was not only influenced by the density of potential prey but was controlled by a number of simultaneously acting environmental factors. The final model, not considering autocorrelation, explained more than 80% of the variance of otolith growth, with larval age as a factor variable showing the strongest significant impact on otolith growth. Otolith growth was further explained by statistically significant ambient environmental factors such as temperature, bottom depth, prey density and turbulence. The GAM analysis, taking autocorrelation into account, explained almost 98% of the variability, with the previous otolith increment showing the strongest significant effect. Larval age as well as ambient temperature and prey abundance also had a significant effect. An alternative approach applied individual‐based model (IBM) simulations on larval drift, feeding, growth and survival starting as exogenously feeding larvae at the back‐calculated positions. The IBM results revealed optimal growth conditions for more than 97% of the larvae, with a tendency for our IBM to slightly overestimate larval growth.

Survival probability of larval sprat in response to decadal changes in diel vertical migration behavior and prey abundance in the Baltic Sea - Hans-Harald Hinrichsen; Myron A. Peck; Jörn Schmidt; Bastian Huwer; Rudi Voss (Limnology and Oceanography, 2010)
We employed a coupled three‐dimensional biophysical model to explore long‐term inter‐ and intra‐annual variability in the survival of sprat larvae in the Bornholm Basin, a major sprat spawning area in the Baltic Sea. Model scenarios incorporated observed decadal changes in larval diel vertical distribution and climate‐driven abiotic and biotic environmental factors including variability in the abundance of different, key prey species (calanoid copepods) as well as seasonal changes, long‐term trends, and spatial differences in water temperature. Climate forcing affected Baltic sprat larval survival both directly (via changes in temperature) and indirectly (via changes in prey populations). By incorporating observed changes in larval diel vertical migration, decadal changes in modeled and observed survival of Baltic sprat agreed well. Higher larval survival (spawning stock biomass) was predicted in the 1990s compared to the 1980s. After changing their foraging strategy by shifting from mid‐depth, low prey environment to near‐surface waters, first‐feeding larvae encountered much higher rates of prey encounter and almost optimal feeding conditions and had a much higher growth potential. Consequently, larvae were predicted to experience optimal conditions to ensure higher survival throughout the later larval and early juvenile stages. However, this behavioral shift also increased the susceptibility of larvae to unfavorable winddriven surface currents, contributing to the marked increase in interannual variability in recruitment observed during the past decade.

Linking growth to environmental histories in central Baltic young‐of‐the‐year sprat, Sprattus sprattus : an approach based on otolith microstructure analysis and hydrodynamic modelling - HANNES BAUMANN; HANS‐HARALD HINRICHSEN; RUDI VOSS; DANIEL STEPPUTTIS; WLODZIMIERZ GRYGIEL; LOTTE W. CLAUSEN; AXEL TEMMING (Fisheries Oceanography, 2006)
Otolith microstructure analysis and hydrodynamic modelling were combined to study growth patterns in young‐of‐the‐year (YoY) sprat, Sprattus sprattus , which were sampled in October 2002 in the central Baltic Sea. The observed ‘window of survival’, approximated by the distribution of back‐calculated days of first feeding (DFF), was narrow compared to the extended spawning season of sprat in the Baltic Sea (mean± SD = 22 June ± 14.1 days) and indicated that only individuals born in summer survived until October 2002. Within the group of survivors, individuals born later in the season exhibited faster larval, but more rapidly decreasing juvenile growth rates than earlier born conspecifics. Back‐calculated larval growth rates of survivors (0.48–0.69 mm day −1 ) were notably higher than those previously reported for average larval sprat populations, suggesting that the YoY population was predominantly comprised of individuals which grew faster during the larval stage. Daily mean temperatures, experienced across the entire YoY population, were derived from Lagrangian particle simulations and correlated with (1) detrended otolith growth and (2) back‐calculated, daily somatic growth rates of survivors. The results showed that abrupt changes in ambient temperature can be detected in the seasonal pattern of otolith growth, and that higher temperatures led to significantly faster growth throughout the entire age range of YoY sprat.